Prevalence of pregnant women with reactive HBsAg in Padang City in 2019 - Utama, Try Genta; Defrin, Defrin (Andalas Obstetrics And Gynecology Journal, 2022)
Introduction: Hepatitis B is an infectious disease that occurs in the liver caused by the hepatitis B virus (HBV). Transmission vertically 95% occurs in the perinatal period (during delivery) and 5% intra uterine. Hepatitis B infection can be acute to chronic. Chronic infection was defined as hepatitis B surface antigen (HBsAg) persistently in blood or serum for more than 6 months with or without active viral replication and evidence of hepatocellular injury or inflammation. Indonesia as a country with high endemicity of Hepatitis B is currently focusing on preventing mother to child transmission (PPIA) because 95% of hepatitis B transmission is vertical, namely from hepatitis B positive mothers to their babies. The number of pregnant women who have been tested for Hepatitis B using the HBsAg Rapid Diagnostic Test (RDT) in 2018 in Indonesia is still relatively small, which is only 39.95% of the target pregnant women who should be examined. In West Sumatra itself occupies the 30th position out of 34 provinces with the percentage of HBsAg reactive pregnant women as much as 0.97%.Objective: This study aims to determine the incidence of pregnant women with reactive HBsAg in the city of Padang.Methods: This research is a descriptive study. The data was taken from the recap of the number of pregnant women who were screened for hepatitis B in all public health centers in the city of Padang during 2019.Result : There are 13,174 (72%) pregnant women who have been tested for HBsAg. Found 131 (0.95%) people with reactive HBsAg. The highest cases were found in the Lubuk Kilangan Public Health Center with 14 cases and the lowest in the opposite health center and Ulak Karang health center with 0 cases. The highest case finding occurred in June with 17 cases and the lowest in November with 7 cases.Conclusion: The prevalence of pregnant women with reactive HBsAg was 0.95% in Padang City in 2019.Keywords: Hepatitis B, HBsAg, Pregnant Women